GRAFTING TRAINING OF ACEH SUPERIOR LOCAL DURIAN AS INITIATION FOR NURSERY IN BUKIT DRIEN VILLAGE SUNGAI RAYA DISCTRICS, EAST ACEH REGENCY - Muhammad Syahril; Rosmaiti Rosmaiti; Adnan Adnan (Global Science Society, 2022)
East Aceh has a high potential for durian diversity. Especially the superior durian plants, most of them are old/expired so there is a fear of death. Propagation of durian plants through seeds will take a long time to bear fruit. To overcome this problem, durian propagation is carried out vegetatively, namely through the grafting method, which requires a shorter fruiting time of around 5 years. Durian propagation by the grafting method is still very rarely done because farmers' knowledge is still limited. For this reason, the Faculty of Agriculture, Universitas Samudra has a moral responsibility to address this problem as well as an effort to preserve germplasm. Farmers' knowledge of grafting, which can also be applied to other crops, can initiate a nursery business. Community service activities have been carried out in Bukit Drien Village, Sungai Raya District, East Aceh Regency. The output achieved was durian seedlings grafted by farmer groups as an indicator of farmers' understanding of the procedures for the grafting process, and the recording of local East Aceh durians.